(untitled) (Biological Sciences - PJSIR, 1999)
The viscosities of cotton seed and walnut seed oils in kerosene diluent have been examined as a function of temperature. The decrease in viscosity values with increase in temperature has been explained in terms oftherrnal vibration resulting in the weakening of intermolecular forces of the oils. Plots of viscosity versus absolute temperature show curvature whereas the plots oflogarithm of viscosity against inverse absolute temperature show linearity for all systems. The activation energy of viscous flow .1Ev ’ the latent heat of vapourization L, and the molar volume of the oil Vm’ were evaluated from that plots: Ev and L, decrease with increase in the volume of kerosene, whilst Vmincreases. The fluidity, which is a measure of the degree of entanglement of the oil molecules, is found to be proportional to the volume occupied by kerosene. It appears that the addition of kerosene uncoils the entangled and aggregated oil molecules.